Psikopatologi Forensik dan Perilaku Kriminal di Indonesia: Studi Kasus Pembunuhan Anak oleh Ibu Kandung yang Mengidap Skizofrenia - Siti Nurmala; Sausan Salsabila; Siti Nuriya Hikma; Helta Puspasari; Dian Anggraeni Rachmawati; Tugimin Supriyadi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Psychopathology, especially mental disorders in Indonesia that are not treated properly can potentially increase the risk of criminal acts by people with mental disorders. This qualitative case study examines the case of child homicide by a mother diagnosed with schizophrenia, revealing the complexity of the interactions between mental disorders and environmental factors. This research emphasizes the role of forensic psychopathology in understanding the relationship between mental disorders and criminal behavior. Schizophrenia, as a serious mental disorder can increase the risk of criminal behavior, especially if adequate treatment is not provided. Symptoms of schizophrenia include delusions and hallucinations which affect emotional control and lead to criminal acts. Social stigma and lack of family awareness of mental disorders worsen the situation. In addition, this research highlights the urgency of increasing awareness and access to mental health services to prevent similar incidents.